MOLECULAR INTERACTION BETWEEN BENZONITRILE AND HEXAMETHYLPHOSPHORIC TRIAMIDE BY 13C NMR T1 RELAXATION TIME STUDIES AND AB INITIO QM CALCULATIONS: EXTENDED INVESTIGATION - Parsaoran Siahaan; Cynthia L. Radiman; Susanto Imam Rahayu; Muhamad A. Martoprawiro; Dieter Ziessow (Indonesian Journal of Chemistry, 2009)
It has been obtained the anisotropy ratio a = T1(ortho-,meta-13C)/T1(para-13C) of dilute solutions of bn change from 1.7 in fa solution and 1.5 in neat bn to 1.0 in HMPT. Thus the anisotropy ratio comes out to be a = 1. In HMPT, obviously, solvent molecules cluster around Ph-CºN in such a way, that non-covalent interactions lead to isotropic reorientational motion like a spherical molecule. To conform with the T1 times, a layer arrangement with at least two HMPT molecules per Ph-CºN seems to be likely. From computational quantum calculations of non-covalent intermolecular interactions and Mie potential analysis, the solute-solvent molecular pairs in  bnּּּHMPT have almost equal interaction energies for the ortho, meta, and para configuration and the layered configurations are energetically permitted